Commoning resistance: Embodying literature as multitude’s collective memories in Aksi Kamisan - Max, Jonathan Irene Sartika Dewi; Muhammad, Harry Isra (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This article examines Aksi Kamisan (Thursday Action) in Samarinda, East Kalimantan, as a contemporary practice of resistance against state-enforced historical amnesia in Indonesia. It addresses the question of how literary traditions of dissent are transmitted and transformed into resources for collective political action. The central thesis is that Indonesia’s Sastra Perlawanan (Literature of Resistance) functions as a lumbung makna, a metaphorical “commons of meaning,” that is actively stewarded, or “commoned,” by social movements. Through an ethnographic case study, this research analyzes the mechanisms by which the literary “archive” is translated into an embodied “repertoire” of political protest. Drawing on an integrated theoretical framework that includes Foucault’s “regime of truth,” Ostrom’s work on the commons, Taylor’s concept of the repertoire, and Hardt and Negri’s theory of the multitude, the study finds that the silent weekly vigil is a performative act of counter-discourse. This act not only challenges the state’s monopoly on historical narratives but also demonstrates how a shared cultural inheritance of resistance is collectively sustained and reactivated. The article concludes that Aksi Kamisan offers a compelling model for understanding the contemporary political efficacy of literature, where cultural memory becomes a vital, living resource for grassroots movements demanding justice and accountability.